Midwives and perinatal mental health: Knowledge, attitudes and learning needs. - Butt, Julia; Huack, Y.; Kelly, G.; Dragovic, M.; Whittaker, P.; Badcock, J. (Elsevier BV, 2015)
Aim: To explore the knowledge, attitudes and learning needs of midwives related to perinatal mental health disorders. Methods: A cross sectional design was used. A survey comprised custom-designed questions and vignettes presenting four disorders. The participants included 238 midwives employed from March to June 2013 at a public tertiary maternity hospital in Western Australia. Results: There was 50.1% response rate with only 37.6% of midwives feeling well-equipped to support women, and 50.2% reporting insufficient access to information. Demand was highest for education on: personality disorders (77.8%); the impact of childbearing on mental health disorders (74.2%); and skills for handling stress and aggression (57.8%). Correct knowledge scores were on average 8 (out of 13), although 2.7% answered more than 11 correctly, and 3.7% scored more than 4 correct. Correct recognition of disorders within four vignettes included depression (93.9%), anxiety (74.8%), a manic episode or bipolar disorder (68.3%) and schizophrenia (65.6%). There were no associations between general knowledge scores and previous mental health experience, recent professional development, or access to information around mental health. The majority endorsed positive beliefs about midwives’ role in mental health assessment and belief in women's recovery (83.5%). The Stereotype Content Model was used to examine how midwives judge a range of social groups including women with and without a mental health disorder. Cluster analysis of warmth and competence ratings revealed negative stereotyping of mental health disorders. Conclusion: Midwives accept it is their role to assess the mental health status of women but many feel ill-equipped to do so and express a strong desire for further knowledge and skills across a range of perinatal mental health topics. Attitudes to recovery are positive but negative stereotypes exist; therefore awareness of potential bias is important to negate their influence on care. Findings will be used to develop a series of perinatal mental health workshops for midwives.